2022
DOI: 10.3389/fimmu.2022.939344
|View full text |Cite|
|
Sign up to set email alerts
|

DCBLD1 Overexpression Is Associated With a Poor Prognosis in Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundDCBLD1 is highly expressed in several kinds of cancer and plays a potential prognostic factor. However, the prognostic value and immune infiltration in head and neck squamous cell carcinoma remain unclear and need further research.Materials and MethodsDCBLD1 expression and clinical information were obtained from the Cancer Genome Atlas (TCGA) database. The mRNA level in cell lines (SCC25 and CAL27) and gingival fibroblasts were detected using quantitative PCR. Cox regression analysis was used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Risk score, clinical stage, and age are found to be important prognostic factors. As nomograms have been widely used as a predictive tool for cancer [ 33 , 34 ], to better understand the clinical characteristics and role of risk scores, we developed nomogram models and validated their high predictive efficiency. As mentioned above, our risk score strongly influenced the prognosis of patients with HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…Risk score, clinical stage, and age are found to be important prognostic factors. As nomograms have been widely used as a predictive tool for cancer [ 33 , 34 ], to better understand the clinical characteristics and role of risk scores, we developed nomogram models and validated their high predictive efficiency. As mentioned above, our risk score strongly influenced the prognosis of patients with HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have suggested that HNSCC is rich with in ltrated immune cells, the progression and prognosis of cancer are tightly related to immune cell in ltration 22 . Furthermore, fatty acid metabolism is directed at supporting speci c cell functions, since the nal outcome of an immune response is determined by cell metabolism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Risk score, clinical stage, and age are found to be important prognostic factors. As nomograms have been widely used as a predictive tool for cancer [33,34], to better understand the clinical characteristics and role of risk scores, we developed nomogram models and validated their high predictive e ciency. As mentioned above, our risk score strongly in uenced the prognosis of patients with HNSC.…”
Section: Discussionmentioning
confidence: 99%